Esophageal and Gastric Cancer Pearl: a nationwide clinical biobanking project in the Netherlands. Issue 5 (30th March 2015) - Haverkamp, L.; Parry, K.; van Berge Henegouwen, M. I.; van Laarhoven, H. W.; Bonenkamp, J. J.; Bisseling, T. M.; Siersema, P. D.; Sosef, M. N.; Stoot, J. H.; Beets, G. L.; de Steur, W. O.; Hartgrink, H. H.; et al.
Summary: Esophageal and gastric cancer is associated with a poor prognosis since many patients develop recurrent disease. Treatment requires specific expertise and a structured multidisciplinary approach. In the Netherlands, this type of expertise is mainly found at the University Medical Centers (UMCs) and a few specialized nonacademic centers. Aim of this study is to implement a national infrastructure for research to gain more insight in the etiology and prognosis of esophageal and gastric cancer and to evaluate and improve the response on (neoadjuvant) treatment. Clinical data are collected in a prospective database, which is linked to the patients' biomaterial. The collection and storage of biomaterial is performed according to standard operating procedures in all participating UMCs as established within the Parelsnoer Institute. The collected biomaterial consists of tumor biopsies, blood samples, samples of malignant and healthy tissue of the resected specimen and biopsies of recurrence. The collected material is stored in the local biobanks and is encoded to respect the privacy of the donors. After approval of the study was obtained from the Institutional Review Board, the first patient was included in October 2014. The target aim is to include 300 patients annually. In conclusion, the eight UMCs of the Netherlands collaborated to establish a nationwide database of clinical information and biomaterial of patients with esophageal and gastric cancer. Due to the national coverage, a high number of patients are expected to be included. This will provide opportunity for future studies to gain more insight in the etiology, treatment and prognosis of esophageal and gastric cancer.